Porous carbon material derived from metal organic framework material, preparation method of porous carbon material and application of porous carbon material in supercapacitor

By using zinc nitrate hexahydrate and trimethylolate as metal organic framework materials, using Zn2+ gasification and evaporation etching technology, porous carbon materials with high specific surface area and high cycle stability were prepared, and carbon in the prior art was solved The problem of poor material circulation performance has achieved supercapacitor electrode materials with high specific capacitance and energy density.

CN119218972APending Publication Date: 2024-12-31CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310777615.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing porous carbon materials have poor cycling performance in supercapacitors, and the metal oxides are highly stable at high temperatures, making them difficult to be reduced to metals, affecting the tracking of the pyrolysis process and the performance of carbon materials.

Method used

Use zinc nitrate hexahydrate and trimethylolate as metal organic framework materials, and controllable defects and micropores are generated through Zn2+ gasification and evaporation etching during the pyrolysis process. Layered porous carbon nanofiber blocks are prepared by soft template method. body, optimize the specific surface area and pore structure of carbon materials.

Benefits of technology

It improves the specific capacitance and energy density of carbon materials, maintains excellent cycling stability, and provides high specific capacity and high energy density electrode materials suitable for supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218972A_ABST
    Figure CN119218972A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological nanomaterials, and particularly relates to a carbon material derived from a metal organic framework material, a preparation method of the carbon material and application of the carbon material in a supercapacitor. According to the invention, trimesic acid and zinc nitrate hexahydrate are used as precursors, a clean, efficient and stable soft template method is selected, and Zn < 2 + > gasification and evaporation etching in a pyrolysis process are utilized, so that the derived carbon material generates a large number of defects and a large number of micropores and mesopores; and a porous material with high specific surface area, high specific capacity and high cycle stability is prepared through drying and high-temperature carbonization process optimization, so that the electrode active material with excellent electrochemical performance is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bionanomaterials, and in particular relates to a porous carbon material derived from a metal organic framework material, a preparation method thereof, and an application of the porous carbon material in a supercapacitor. Background Art

[0002] At present, the increasing shortage of energy and the extensive use of fossil fuels have caused global pollution, deterioration of air quality and energy security. Therefore, new electrochemical energy storage and conversion devices that are environmentally friendly, efficient and sustainable have attracted increasing interest. Supercapacitors (SCs) have received great attention as one of the most promising electrochemical energy conversion and storage devices. Supercapacitors have good application prospects in many fields such as new energy vehicles and aerospace electronic products due to their high power density, fast charge and discharge rate, super durability, safety and reliability.

[0003] Recently, porous carbon materials have emerged as one of the most promising candidates for supercapacitor electrode materials due to their excellent properties such as controllable porosity, high cycle stability, large specific surface area, and good electrical conductivity. These materials have led to a class of supercapacitors called electric double-layer capacitors (EDLCs), which have electrochemical stability and physical adsorption and desorption processes, so they can provide ultra-high power density and excellent cycle life. Carbon materials are usually obtained from carbon-rich precursors through high-temperature reactions under inert atmospheres accompanied by complex chemical processes, but their structural evolution process is not obvious. In addition, for EDLCs, their performance is affected by properties such as pore structure, pore size distribution, and surface area. However, the behavior of different components during the chemical process affects the properties and characteristics of the final product. Therefore, it is necessary to have a deep understanding of the surface composition of carbon materials to control their accurate layered structure and effectively track their formation process.

[0004] Metal-organic frameworks (MOFs) have been intensively studied as suitable carbon precursors because of their controllable pore size and composition, which have a positive effect on the pyrolysis process tracking of the target products. However, most metal oxides in carbon-rich materials are very stable at relatively high temperatures, except for zinc (Zn), which is not easily reduced to their respective metals. In addition, zinc, as a transition metal, can be evaporated at moderate temperatures (<1000°C) due to its boiling point of 906°C. Therefore, in order to track the pyrolysis process of carbon-rich porous materials, it is suitable to use zinc as a carbon precursor. The key pyrolysis process when the temperature rises from 30°C to 900°C is mainly attributed to the reduction of ZnO and the volatilization of Zn. However, the reduction process of ZnO has not been clearly demonstrated, and no zinc clusters can be observed during the entire pyrolysis process. Metal-organic frameworks have been demonstrated as precursors of porous carbon materials, which usually have large surface areas and high specific capacitances, but their cycling performance is unsatisfactory due to the pseudocapacitive properties of metal- or nitrogen-containing chemicals. Summary of the invention

[0005] The purpose of the present invention is to provide a porous carbon material derived from a metal organic framework material with large specific surface area, high specific capacity and energy density, and excellent cycle performance in response to the above technical problems.

[0006] The above-mentioned purpose of the present invention is implemented through the following technical solutions:

[0007] A porous carbon material derived from a metal organic framework material, wherein the specific surface area of ​​the carbon material is 186-783m 2 g -1 , pore volume is 0.10-0.44cm 3 g -1 , pore size is 5-10nm.

[0008] Preferably, the specific surface area of ​​the carbon aerogel is 780-785m 2 g -1 , pore volume is 0.40-0.50cm 3 g -1 , pore size is 1-3nm.

[0009] The present invention also provides a method for preparing a porous carbon material derived from a metal organic framework material, the method comprising the following steps: S1: dissolving zinc nitrate hexahydrate and trimesic acid in water, and stirring to obtain a mixed solution;

[0010] S2: Wash with water and centrifuge to obtain a white solid powder;

[0011] S3: The white powder is freeze-dried and then carbonized to obtain a porous carbon material derived from a metal organic framework material.

[0012] Most metal chemicals are very stable at high temperatures, but only Zn 2+ It can be reduced to metal Zn and then evaporate and diffuse at a temperature above 800°C. 2+ Metal-organic framework materials with ligands containing only O and C atoms serve as ideal pore-forming templates and carbon sources, improving the specific capacitance and energy density of EDLC carbon materials while maintaining their unique cycling performance.

[0013] The porous carbon material prepared by the soft template method of the present invention is to use Zn-1,3,5-benzenetricarboxylic acid (BTC) (Zn-BTC) carbonization to manufacture a layered porous carbon nanofiber block. 2+ ions have a strong affinity and many contact active sites, and then react with Zn during the pyrolysis process. 2+ Gasification and evaporation etching are performed to produce controllable defects and micropores and mesopores in the derived carbon material. The present invention benefits from the controllable defects and micropores and mesopores, so that the carbon material has a larger specific surface area and provides a higher specific capacitance. The symmetrical supercapacitor constructed with the carbon material of the present invention has a higher specific capacity, significant energy and power density and excellent stability, which indicates its excellent overall energy storage performance and can achieve promising practical applications.

[0014] Preferably, in step S1, the molar ratio of zinc nitrate hexahydrate to trimesic acid is 1.5: 1. Different molar ratios will affect the pore structure and cross-linking degree of the carbon material.

[0015] In the step S1 of the present invention, zinc nitrate hexahydrate is used as a precursor of the metal organic framework material. If the amount added is too much, a large number of defects will appear in the final carbon material, and too many defects will lead to a decrease in specific capacitance. If the amount added is too little, Zn 2+ It only plays a little role in gasification and evaporation etching, so the specific surface area is not very large, which makes it impossible to significantly improve the performance of carbon materials.

[0016] Preferably, the heating temperature in the mixed solution is 20-100°C.

[0017] In the present invention, zinc nitrate hexahydrate and the organic ligand trimesic acid are slightly soluble in water, and the metal ions and the organic ligands enter each other's system by diffusion, and a self-assembly reaction occurs to obtain the MOF material.

[0018] More preferably, the heating temperature in step S1 is 80° C., so that the two can be completely and evenly mixed in water.

[0019] Preferably, the freeze-drying time in step S3 is 12-48 hours.

[0020] Preferably, the carbonization temperature in step S3 is 700-1000° C. and the time is 1-3 h.

[0021] More preferably, the carbonization temperature is 1000°C.

[0022] More preferably, the carbonization is performed in an inert atmosphere such as nitrogen or argon.

[0023] The present invention also provides an application of a carbon material derived from a metal organic framework material in a supercapacitor, wherein the carbon material is used as an electrode in the supercapacitor.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention uses metal organic framework materials as precursors, utilizes Zn2+ gasification and evaporation etching during pyrolysis to produce a large number of defects and a large number of micropores and mesopores, and then optimizes the drying and high-temperature carbonization process to obtain carbon materials with high specific surface area, specific capacity and high cycle stability, thereby providing electrode active materials with excellent electrochemical properties.

[0026] 2. The method of the present invention effectively enhances the structural stability of the carbon material, making it have good cycle stability.

[0027] 3. The present invention uses metal organic framework-based carbon materials for supercapacitors, and as electrode active materials, supercapacitors with high specific capacitance and high stability can be prepared.

[0028] 4. The method of the present invention is simple and controllable, has good repeatability, is easy to industrialize, and can be promoted and applied in the field of green energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the TEM image of the carbon material prepared in Example 1.

[0030] Figure 2 The cyclic voltammetry curves of the carbon material electrodes of Examples 1-4 were measured at 100 mV / s.

[0031] Figure 3 The charge and discharge curves of the carbon material electrodes of Examples 1-4 measured at 0.5 A / g.

[0032] Figure 4 This is the cycle stability curve of the two electrodes of the carbon material electrode in Example 1.

[0033] Figure 5 This is a curve of the energy density and power density of the two electrodes of the carbon material in Example 1. DETAILED DESCRIPTION

[0034] The technical scheme of the present invention is further described below by specific embodiments. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in this area, and the methods used in the embodiments are all conventional methods in this area. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention.

[0035] Embodiment 1:

[0036] S1: Add 8 g of zinc nitrate hexahydrate and 3.64 g of trimesic acid and stir at 80°C for 2 hours to fully react, and the obtained reaction product is thoroughly washed with deionized water;

[0037] S2: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0038] S3: Heat to 1000℃ at a rate of 5℃ / min, keep warm for 2h, take out the tube resistance furnace after cooling, and obtain a specific surface area of ​​893m 2 g -1 , pore volume is 0.3cm 3 g -1 , porous carbon material with a pore size of 6.71nm.

[0039] Embodiment 2:

[0040] S1: Add 8g zinc nitrate hexahydrate and 3.64g trimesic acid and stir at 80°C for 2 hours to fully react, and wash the obtained reaction product thoroughly with deionized water;

[0041] S2: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0042] S3: Heat to 700℃ at a rate of 5℃ / min, keep warm for 2h, take out the tube resistance furnace after cooling, and obtain a specific surface area of ​​893m 2 g -1 , pore volume is 0.3cm 3 g -1 , porous carbon material with a pore size of 6.71nm.

[0043] Embodiment 3:

[0044] S1: Add 8 g of zinc nitrate hexahydrate and 3.64 g of trimesic acid and stir at 80°C for 2 hours to fully react, and the obtained reaction product is thoroughly washed with deionized water;

[0045] S2: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0046] S3: Heat to 800℃ at a rate of 5℃ / min, keep warm for 2h, take out the tube resistance furnace after cooling, and obtain a specific surface area of ​​893m 2 g -1 , pore volume is 0.3cm 3 g -1 , porous carbon material with a pore size of 6.71nm.

[0047] Embodiment 4:

[0048] S1: Add 8 g of zinc nitrate hexahydrate and 3.64 g of trimesic acid and stir at 80°C for 2 hours to fully react, and the obtained reaction product is thoroughly washed with deionized water;

[0049] S2: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0050] S3: Heat to 900℃ at a rate of 5℃ / min, keep warm for 2h, take out the tubular resistance furnace after cooling, and obtain a specific surface area of ​​893m 2 g -1 , pore volume is 0.3cm 3 g -1 , porous carbon material with a pore size of 6.71nm.

[0051] The carbon material sample of the metal organic framework material obtained in Example 1 was scanned using a transmission electron microscope to characterize its morphology and structure. Figure 1 It can be seen that the carbon material prepared in Example 1 has a rich chemical structure, densely arranged nanopores, and a dense graphitized carbon layer with high conductivity. It can be seen that the prepared carbon material has a large pore structure and conductivity.

[0052] The carbon materials obtained in Examples 1 and 2, 3, and 4 were used as supercapacitor electrodes, named A, B, C, and D, respectively, and coated on nickel foam and clamped on an electrode clamp. In a three-electrode system, the Hg / HgO electrode was used as a reference electrode, the platinum sheet electrode was used as a counter electrode, and a 6M KOH solution was used as an electrolyte, and its electrochemical performance was tested at room temperature.

[0053] Figure 2 1 is the cyclic voltammetry curve of several carbon materials at a scan rate of 100 mV / s. It is found that the carbon material obtained in Example 1 has a larger rectangular area, indicating that the electrode has a higher energy storage capacity.

[0054] Figure 3 The charge and discharge curves were measured at 0.5A / g. The specific capacitances of the electrodes were calculated to be 343F / g, 199F / g, 266F / g and 293F / g, which were consistent with the results of the cyclic voltammetry curves.

[0055] Figure 4 This is the cycle stability curve of the two electrodes of electrode A measured under 4A / g conditions. After 30,000 cycles, the cycle retention rate is close to 100%, indicating that the electrode has good cycle stability.

[0056] Figure 5 This is a curve diagram of the power density and energy density of the two electrodes of electrode A. The energy density is 8.69Wh / kg under the condition of power density of 250W / kg, and the energy density is 4.44Wh / kg under the condition of power density of 9999W / kg, indicating that the electrode has a very high energy density.

[0057] It can be seen from the above results that compared with the performance of metal organic framework material-based supercapacitors in the prior art, the method of the present invention effectively increases the specific capacity of the prepared carbon material and maintains the cycle stability well. Selecting a suitable metal organic framework material as a soft template and carbon source, and optimizing the pore structure through simple stirring, drying and high-temperature carbonization processes, not only effectively enhances the specific surface area of ​​the carbon material and introduces adjustable defects, but also provides a good performance electrode material for supercapacitors, which can be used for the preparation of green energy storage devices with high specific capacitance, long cycle life and high energy density.

[0058] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0059] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0060] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A porous carbon material derived from a metal organic framework material, characterized in that: The specific surface area of ​​the carbon material is 186-783 m 2 g -1 , pore volume is 0.10-0.44cm 3 g -1 , pore size is 5-10nm.

2. The porous carbon material derived from a metal organic framework material according to claim 1, characterized in that: The specific surface area of ​​the porous carbon material is 780-785 m 2 g -1 , pore volume is 0.40-0.50cm 3 g -1 , pore size is 1-3nm.

3. A method for preparing a porous carbon material derived from a metal organic framework material as claimed in claim 1, characterized in that: The method comprises the following steps: S1: dissolving zinc nitrate hexahydrate and trimesic acid in water, and stirring to obtain a mixed solution; S2: Wash with water and centrifuge to obtain a white solid powder; S3: The white powder is freeze-dried and then carbonized to obtain a porous carbon material derived from a metal organic framework material.

4. The method for preparing a porous carbon material derived from a metal organic framework material according to claim 1, characterized in that: In step S1, the molar ratio of zinc nitrate hexahydrate to trimesic acid is (0.5-2):

1.

5. The method for preparing a porous carbon material derived from a metal organic framework material according to claim 1, characterized in that: In step S1, the heating temperature in the mixed solution is 20-100°C.

6. The method for preparing a porous carbon material derived from a metal organic framework material according to claim 1, characterized in that: The freeze-drying time in step S3 is 12-48 hours.

7. The method for preparing a porous carbon material derived from a metal organic framework material according to claim 1, characterized in that: The carbonization temperature in step S3 is 700-1000° C., and the carbonization time is 1-3 hours.

8. A use of the porous carbon material derived from the metal organic framework material as claimed in claim 1 in a supercapacitor, characterized in that: The porous carbon material according to any one of claims 1 to 7 is used as an electrode in a supercapacitor.